HOW TO MANAGE YOUR FAMILY BUSINESS the 10 imperatives for success. - FAHED-SREIH, JOSIANE (CAMBRIDGE SCHOLARS PUBLIS, 2019)
This book details ten of the most important aspects for success in a family business, and discusses how to begin the development of a common vision to deploy within the family firm. It uses the Middle East as an example of a patriarchy and its values, and how these may be transmitted to the family business and the next generation. Such traditions and culture are often integrated within the mindset of the owner and are then established in the company's vision. The book serves as a guideline to the 'dos and don'ts' of the family business scene and how to affect the firm either positively or nega.